Acute ingestion of a ketone monoester without co-ingestion of carbohydrate improves running economy in male endurance runners - Brady, A. J.; Egan, B. (Medicine & Science in Sports & Exercise, 2024)
Purpose Acute ingestion of a ketone monoester, with and without co-ingestion of carbohydrate, was investigated for effects on running economy (RE), time to exhaustion (TTE), and other related indices of endurance running performance.